ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI PERGANTIAN KANTOR AKUNTAN PUBLIK PADA PERUSAHAAN MANUFAKTUR DI INDONESIA (Students' Journal of Accounting and Banking, 2014)
This study isa test management turnover, financial distress, Size of public account officer and size company on the analysisof factors-factors that affect the turn public accounting firm. In accordance with agency theory that a relationship exists when one part(the principal) hire another part(the agent) to perform a service, and then delegate decision-making authority to the agent. In this research, the researcher used purposive sampling and obtained 136sample firms. Using logistic regression analysis to explain the relationship between these variables. The results of the statisticalt test showed that only the financial distress affecting any change KAP, while management turnover, size of public account officer and size company does not affect the change of KAP.Keywords: auditor turnover, management turnover, financial distress, Size of public account officer and size company